Legal Policy on Human Trafficking Crimes - Abdul Rahman Prakoso; Putri Ayu Nurmalinda (IJCLS (Indonesian Journal of Criminal Law Studies), 2018)
The crime of human trafficking still become problem in people's lives. Human trafficking undertaken includes the process of hiring up to the act of buying and selling people. The existence of Law Number 21 of 2007 concerning the Eradication of Crime of Human Trafficking as protection for trade acts. The legal policy in the realm of human trafficking is not only about central government elements but also related to the policies issued by the local government. The law as an existing regulatory instrument in Indonesia is based on the existence of regional policy to protect its citizens. Trafficking cannot be separated from various parties. This concernsvarious aspects of the community elements involved in it. There is a need for comprehensive prevention to avoid trafficking. In this case both the office and the law enforcers must play a role in the prosecution and protection of trafficking.